Study of Augmented Reality Based Applications in Education - Pal Yadav, Amar; Singh, Sachin; Chaudhary, Manish (Research Parks Publishing LLC, 2025)
A technology known as augmented reality mixes and communicates with both virtual and actual situations. Applications for augmented reality are being used in many industries, but education is the most significant. We can combine actual and virtual information, augmented reality (AR) technology helps kids study while strengthening their connection to their physical surroundings. Virtual reality technology, which is still in development, enables students to learn challenging subjects in a pleasant and simple method. Students can learn more about the objects by interacting with them in virtual environments. We can organise virtual excursions to museums and zoos in a completely different nation and work with teacher as if they were physically present. The use of augmented reality technology in various facets of education was demonstrated in this context. According to the recommendations offered at the end of the research, educators should carefully investigate prepared portions and practise them in their classes.